Lateral cephalometric analysis for treatment planning in orthodontics based on MRI compared with radiographs: a feasibility study in children and adolescents - Heil, Alexander; Lazo Gonzales, Eduardo; Hilgenfeld, Tim; Vollmuth, Philipp; Bendszus, Martin; Heiland, Sabine; Ozga, Ann-Kathrin; Sommer, Andreas Berthold; Lux, Christopher J.; Zingler, Sebastian (PLOS ONE, 2017)
The objective of this prospective study was to evaluate whether magnetic resonance imaging (MRI) is equivalent to lateral cephalometric radiographs (LCR, “gold standard”) in cephalometric analysis. Methods The applied MRI technique was optimized for short scanning time, high resolution, high contrast and geometric accuracy. Prior to orthodontic treatment, 20 patients (mean age ± SD, 13.95 years ± 5.34) received MRI and LCR. MRI datasets were postprocessed into lateral cephalograms. Cephalometric analysis was performed twice by two independent observers for both modalities with an interval of 4 weeks. Eight bilateral and 10 midsagittal landmarks were identified, and 24 widely used measurements (14 angles, 10 distances) were calculated. Statistical analysis was performed by using intraclass correlation coefficient (ICC), Bland-Altman analysis and two one-sided tests (TOST) within the predefined equivalence margin of ± 2°/mm.
Gesehen am 21.07.2017